The Impact of Applied Informatics and Digitalization of Traditional Arts - Cahyaningrum, Yuniana; Prasetyo, Ilyas Adhi; Abdullah, Maesa (Universitas Pendidikan Indonesia (UPI), 2024)
This article examines the role of applied informatics in the digitization of traditional arts as an effort to bridge the gap between culture and technology. In the context of globalization and rapid technological advancement, traditional arts face challenges to remain relevant and preserved. Digitization offers innovative solutions that enable the documentation, modernization, and distribution of traditional artworks through various digital platforms. Through methods such as 3D modeling, Augmented Reality (AR), and Virtual Reality (VR), the digitization process not only preserves authenticity and cultural values, but also introduces new ways to appreciate and experience art. The study also highlights how applied informatics facilitates the accessibility of traditional artworks, both through virtual exhibitions and e-commerce platforms, which expands the audience reach and increases marketing opportunities for artists. In addition, the article emphasizes the importance of arts education and training that uses digital technology to teach techniques and cultural contexts to the younger generation. The results of the study show that the integration of technology in traditional arts not only contributes to cultural preservation but also creates opportunities for artistic innovation and deeper interaction with cultural heritage. Thus, this article is expected to provide insight for academics, artists, and practitioners in the field of applied informatics about the importance of collaboration between art and technology in preserving culture in the digital era.